Arah Pergerakan Perubahan Leksikon Tipe Konservatif Pada Enklave Jawa Carita, Banten - M Suryadi (Nusa: Jurnal Ilmu Bahasa dan Sastra, 2018)
The purpose of this research is to find the direction of movement and change of lexicon which is located in Javanese enclave, Carita, Banten. Methods of data collection using observation and interview methods: tapping techniques, fishing techniques, recording techniques, and tekik notes. The method of analysis used is reconstruction method and tree root direction method The research findings that the Java enclave region, Carita, in the Sundanese language area, still holds many relics and original lexicons.The relics lexicon form is a lexicon that is derived directly from the ancient Javanese language without any slight change, either form or meaning.The original form of lexicon is a lexicon that changes at the time of inheritance. Changes that occur in the lexicon can be explained through linguistic rules.The direction of the movement of the relics and the original form of the Javanese dialect of Carita has a tendency of vertical direction, ie the direct inheritance direction of the ancient Javanese language.The direction of the movement of innovative shape changes tends to be horizontal, ie the direction of change that adapts the rules of Sundanese and Malay.